Hamilton paths in Cayley graphs on generalized dihedral groups - Alspach, Brian (Ars mathematica contemporanea, 2010)
We investigate the existence of Hamilton paths in connected Cayley graphs on generalized dihedral groups. In particular, we show that a connected Cayley graph of valency at least three on a generalized dihedral group, whose order is divisible by four, is Hamiltonconnected, unless it is bipartite, in which case it is Hamilton-laceable.
Keywords: grafi; matematika; teorija grafov